Extensive genotypic diversity in a recombining population of the apicomplexan parasite Theileria parva - Katzer, F.; Ngugi, D.; Oura, C.; Bishop, Richard P.; Taracha, E.L.N.; Walker, A.R.; McKeever, Declan J. (American Society for Microbiology, 2006)
We evaluated sexual recombination in the apicomplexan parasite Theileria parva using genome-wide marker analysis of haploid sporozoite populations obtained from infected Rhipicephalus appendiculatus ticks. Analysis of 231 parasite clones derived by in vitro infection of bovine lymphocytes revealed 48 distinct combinations of 64 polymorphic marker loci. One genotype accounted for more than 75% of the clones, and the population was highly inbred with respect to this. The occurrence of frequent recombination was evident from reassortment of contiguous markers in blocks, with some recombination occurring within blocks. Analysis of four polymorphic loci encoding antigens targeted by protective cytotoxic-T-lymphocyte responses confirmed that these loci reassort, both within and between chromosomes, suggesting that recombination may influence immune recognition. Marker analysis of a panel of 142 clones derived from the population after an additional passage through a calf and the same tick colony revealed 18 genotypes, with the original dominant genotype accounting for 75% of the population and a higher level of inbreeding with respect to it in the remaining clones. Selected marker analysis of genomic DNA from these stabilates and the two preceding generations of the isolate, each derived from distinct tick colonies, revealed shifts in population structure with each generation, suggesting that the tick vector may impose nonrandom selective pressure on the parasite.